Determination of concrete strength and stiffness after fire simulation through multiple regression models between wave propagation and temperature - Silva, Rodrigo Rogerio Cerqueira da Silva; Gomes, Yara Balbino (Revista ALCONPAT, 2024)
The aim of this research was to evaluate the behaviour of the physical, mechanical and elastic parameters of concretes made with different water/cement ratios, subjected to different temperature levels, using ultrasonic wave propagation. After exposure to high temperatures, cylindrical and prismatic concrete samples were subjected to slow and abrupt cooling, demonstrating the influence of the type of cooling on compressive strength, modulus of elasticity, mass loss and wave propagation speed. Statistically significant multiple regression models were developed at the 95% confidence level as predictors of concrete strength and stiffness through the velocities obtained by ultrasound testing, enabling the integrity of structures to be monitored and verified after fire situations.